Analysis of Asean’s Shock in The Discourse on Establishing Asean Currency Unit (Acu) - Susi Susanti (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
The discourse of the establishment of ASEAN single currency is the vision of ASEAN in 2020 with the aim to facilitate the stabilization of the regional exchange rate. The region that will form a single currency must have the same trade pattern criteria, symmetrical macroeconomic shocks and similar development economics characteristics. However, the economics indicators of ASEAN region are still inbalances. This study aims to analyze the shocks response of economic indicators in ASEAN-10. The variables in this research are Consumer Price Index (CPI), Real GDP and Trade Balance from ASEAN countries. This research model is Vector Error Correction Model. The are low correlation between Consumer Price Index (CPI), Real GDP and Trade Balance in ASEAN. The shock response from ASEAN countries to shocks that occurred in Singapore showed varying results and not symmetrical. This is shows that the requirement of formation of single currency has not been fulfilled. The result of the decomposition variant also shows that Singapore's economic turmoil is still dominantly influenced by internal conditions. However, the decomposition variant of GDP Rill shows that Laos has a higher role compared to Singapore due to the cooperative relationship between the two countries.